A retrospective analysis of bleeding risk with rivaroxaban, enoxaparin, and aspirin following total joint arthroplasty or revision. Issue 7 (22nd June 2021) - Watts, Paula J.; Kopstein, Michael; Harkness, Weston; Cornett, Brendon; Dziadkowiec, Oliwier; Hicks, M. Elizabeth; Hassan, Shakib; Scherbak, Dmitriy
Abstract: Study Objective: Rivaroxaban, enoxaparin, and aspirin are commonly used medications for thromboprophylaxis following lower extremity joint arthroplasty or revision. Previous research has demonstrated efficacy in preventing venous thromboembolism with each medication, however, the comparative risk of bleeding between them remains poorly understood. The aim of this study was to compare the odds of bleeding between rivaroxaban, enoxaparin, and aspirin following lower extremity joint arthroplasty or revision. Design: This is a 3‐year retrospective cohort study. Setting: Data were obtained from 148 facilities across 55 states and territories of the United States. Patients: This study included 85, 938 patients who underwent hip or knee arthroplasty or revision. Intervention: Patients received enoxaparin, rivaroxaban, or aspirin as monotherapy for thromboprophylaxis. Measurements: The primary outcome was all bleeding, classified as major or minor bleeding, occurring in the 40 days following surgery. The secondary outcome was venous thromboembolism. Main Results: Among 85, 938 patients, 10, 465 received rivaroxaban, 14, 047 received enoxaparin, and 61, 426 received aspirin. Bleeding occurred in 126 (1.20%) patients with rivaroxaban, 253 (1.80%) with enoxaparin, and 611 (0.99%) with aspirin. There was a significant increase in odds of bleeding in the enoxaparin compared to aspirin group odds ratio (OR) 1.18, 95% confidence interval (CI) 1.01–1.38, p = 0.042), and a trend toward increased odds of bleeding in rivaroxaban compared to aspirin group (OR 1.21, 95% CI 0.99–1.47, p = 0.058) and rivaroxaban compared to enoxaparin (OR 1.03, 95% CI 0.82–1.28, p = 0.827). Odds of venous thromboembolism were not statistically significant between all three study medications. Conclusions: Among rivaroxaban, enoxaparin, and aspirin used for thromboprophylaxis in knee and hip arthroplasty or revision, aspirin had significantly decreased odds of bleeding complications compared to enoxaparin. Although not statistically significant, aspirin also had a trend toward decreased odds of bleeding complications compared to rivaroxaban. Our study results suggest that aspirin is a safer alternative for use in postoperative thromboprophylaxis following lower extremity joint arthroplasty or revision.